Respuesta :

Answer:

The solution is obtained by adding the two equations.

The solution is: (x, y) = ([tex]$ - \frac{2}{3} $[/tex], [tex]$ - \frac{7}{3} $[/tex])

Step-by-step explanation:

We are given two equations with two variables. The strategy is to eliminate one variable and solve for both the variables.

The two equations are:

[tex]$ 7x + y = - 7 \hspace{15mm} \hdots (1) $[/tex]

[tex]$ 2x - y = 1 \hspace{15mm} \hdots (2) $[/tex]

Adding both the equations, we get:

[tex]$ 7x + 2x + y - y = - 7 + 1 $[/tex]

[tex]$ \implies 9x = - 6 $[/tex]

[tex]$ \implies x = - \frac{2}{3} $[/tex]

Substituting the value of 'x', we get the value of y.

We substitute in (2). [Can be substituted in any equation].

We get: y = 2x - 1

[tex]$ \imples y = 2\bigg(\frac{-2}{3}\bigg) - 1 $[/tex]

[tex]$ \implies -\frac{4}{3} - 1 $[/tex]

[tex]$ \implies y = -\frac{7}{3} $[/tex]

So, we get the corresponding values of x and y which is the solution of the two equations.